Efektivitas Kebijakan Restrukturisasi Pembiayaan Bermasalah pada Masa Pandemi Covid-19 - Arli Sutanti; Peni Haryanti (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
The Indonesian government through the task force for handling the corona virus stated that the World Health Organization had given an official statement on March 9, 2020 regarding COVID-19 which was declared a pandemic. As a result of this, the banking industry experienced a decline in income caused by debtors who had difficulty paying their obligations due to declining sales due to the COVID-19 pandemic. Banks needed to restructure to save themselves from much larger losses. This statement is supported by the POJK issued by the OJK at the POJK 2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of Corona Virus Disease 2019 at Number 11/POJK.03/2020. This study aims to determine the effectiveness of the financing restructuring policy on non-performing financing during the pandemic. From the results of research conducted by researchers using three data collection techniques, namely observation, interviews, and documentation, it can be concluded that the implementation of the financing restructuring policy due to the COVID-19 pandemic at BPRS Lantabur Tebuireng has been implemented effectively in reducing Non Performing Finance. The implementation of financing restructuring is considered to be able to assist BPRS Lantabur Tebuireng in arranging appropriate payment schemes for debtors whose businesses are affected by the COVID-19 pandemic.